Accounting for local impacts of photovoltaic farms: The application of two stated preferences approaches to a case-study in Portugal - Botelho, Anabela (2017)
Renewable energy sources for electricity generation are unequivocally more environmentally friendly than the traditional sources, but are not impact-free. Given the potential for solar photovoltaic energy to contribute to the energy mix in some countries, it is timely to carefully consider the potential environmental costs of operation of photovoltaic farms, which are experienced by the local population, while the general benefits accrue to all. We apply the contingent valuation method to a sample of local residents close to three selected photovoltaic farms in Portugal. Also, we design a discrete choice experiment to elicit the valuation of specific adverse impacts of electricity generation through photovoltaic energy by national residents. Our results show that the value elicited in the vicinity of the photovoltaic farms is non-negligible. On the other hand, national residents ponder the trade-offs implied by the choice sets and value positively the different adverse local impacts. Both of these estimates, in conjunction or independently, can be used to fully account for this often neglected cost of solar energy. Furthermore, we argue that when studying the public acceptance of renewables, using stated preference methods explicitly presents the trade-offs between negative impacts and costs, contributing to more realistic portrayal of public opinion.